2011
DOI: 10.1158/1055-9965.epi-11-0359
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers Related to One-Carbon Metabolism as Potential Risk Factors for Distal Colorectal Adenomas

Abstract: Background: Efficient one-carbon metabolism, which requires adequate supply of methyl group donors and B-vitamins, may protect against colorectal carcinogenesis. However, plasma folate and vitamins B2 and B12 have inconsistently been associated with colorectal cancer risk, and there have been no previous studies relating plasma concentrations of methionine, choline, and betaine to this outcome.Methods: This study comprised 10,601 individuals, 50 to 64 years of age, participating in the Norwegian Colorectal Can… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 48 publications
0
31
1
Order By: Relevance
“…notably, this is consistent with earlier studies. [12][13][14] absolute risk calculations in terms of marginal risk differences for high versus low plasma levels of betaine and methionine yielded estimated average reductions of colorectal cancer occurrence of approximately 200 cases per 100,000 individuals in the study cohort. given the population-based nature of the cohort, 16,17 the potential effects of higher methionine and betaine concentrations on colorectal cancer risk may be substantial.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…notably, this is consistent with earlier studies. [12][13][14] absolute risk calculations in terms of marginal risk differences for high versus low plasma levels of betaine and methionine yielded estimated average reductions of colorectal cancer occurrence of approximately 200 cases per 100,000 individuals in the study cohort. given the population-based nature of the cohort, 16,17 the potential effects of higher methionine and betaine concentrations on colorectal cancer risk may be substantial.…”
Section: Discussionmentioning
confidence: 99%
“…4,7 a greater understanding of the relative contribution of components in the one-carbon metabolism, including methionine and factors in the choline oxidation pathway, to colorectal cancer risk may therefore provide new insight into the mechanistic role of onecarbon metabolism in carcinogenesis. 11 to the best of our knowledge, only two previous prospective studies of colorectal cancer, nested within the european Prospective investigation into cancer and nutrition (ePic) cohort and the Women's Health initiative (WHi), 12,13 and one cross-sectional study of colorectal adenoma, 14 have addressed the role of circulating one-carbon metabolites other than folate in colorectal cancer development. inverse risk associations for betaine and null results for choline were observed in all three studies, [12][13][14] and an inverse association to colorectal cancer for methionine was reported in the ePic study.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, the prospective Health Professionals Follow-up Study found no association with dietary choline or betaine intakes and CRC risk, even when stratifying choline by its metabolic derivatives (Lee et al 2010 ). However, in the Norwegian Colorectal Cancer Prevention Trial, the occurrence of high-risk distal colorectal adenomas was inversely associated with plasma betaine concentrations but not with choline (de Vogel et al 2011a ). Interestingly, in the Nurses Health Study, dietary choline was positively associated, yet betaine was inversely associated with risk of colorectal adenoma when comparing the highest quintile of concentrations to the lowest (Cho et al 2007a ).…”
Section: Colorectal Cancermentioning
confidence: 96%
“…Apart from the folates, some [87,88], though not all [89], epidemiological studies that have examined the issue suggest a protective effect of other nutrients linked to one-carbon metabolism against colorectal cancer, including methionine and betaine. Further studies to determine whether such potentially beneficial effects are associated with consistent epigenetic patterns in the colorectal mucosa would be valuable.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%